2016
DOI: 10.1159/000449172
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitrectomy Combined with Subretinal Recombinant Tissue Plasminogen Activator for Subretinal versus Subpigment Epithelial versus Combined Hemorrhages

Abstract: Background: The aim of this study was to compare the outcomes after subretinal recombinant tissue plasminogen activator (rtPA) treatment for subretinal hemorrhages (SRH), subpigment epithelial hemorrhages (SPH), and combined subretinal and subpigment epithelial hemorrhages (CH). Methods: An observational analysis of patients treated with subretinal rtPA was performed. The primary endpoint was the assessment of visual improvement (best-corrected visual acuity, BCVA) after surgery. Secondary endpoints were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…For any manipulation below the retinal pigment epithelium, there must be considerations about a potential benefit against the risk of provoking a RIP. Our study results allow for a clinical presurgery assessment of the underlying case, based on its anatomical characteristics [2] . However, the case of Fotis et al [1] is important, since it strikingly demonstrates the possibility of a SPH displacement with subretinal rtPA treatment.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…For any manipulation below the retinal pigment epithelium, there must be considerations about a potential benefit against the risk of provoking a RIP. Our study results allow for a clinical presurgery assessment of the underlying case, based on its anatomical characteristics [2] . However, the case of Fotis et al [1] is important, since it strikingly demonstrates the possibility of a SPH displacement with subretinal rtPA treatment.…”
mentioning
confidence: 82%
“…We are very grateful to Fotis et al [1] for their interest in our recently published study [2] that presents the structural and functional outcome after pars plana vitrectomy combined with subretinal recombinant tissue plasminogen activator (rtPA) treatment for isolated subretinal, subpigment epithelial (SPH), and combined hemorrhages. Here, we would like to respond to the questions that were raised by the authors:…”
Section: Dear Editormentioning
confidence: 99%
“…They concluded that vitrectomy combined with subretinal recombinant tissue plasminogen activator (rtPA) injection and gas or air tamponade has a strong functional and anatomical effect on both subneuroretinal haemorrhage (SRH) and combined subneuroretinal and sub-retinal pigment epithelial (RPE) haemorrhage (CH) and also seems to slightly improve the anatomical outcome in subpigment epithelial haemorrhage (SPH) [1] .…”
Section: Dear Editormentioning
confidence: 99%
“…This method finally resulted in better functional outcome (Heriot WJ 1996, Paper presented at the American Academy of Ophthalmology Annual Vitreoretinal Update in Chicago, IL). Since then, more invasive methods of rtPA-assisted hemorrhage displacement during vitrectomy have been described [10][11][12][13]. Further studies showed that additive anti-VEGF treatment could help to prevent recurrence of submacular hemorrhage [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed that additive anti-VEGF treatment could help to prevent recurrence of submacular hemorrhage [14,15]. Although intravitreal rtPA seems to be effective the recent trend has been toward the subretinal administration of rtPA during vitrectomy combined with either gas or air tamponade since it has been proved to be a promising combination [4,13,16].…”
Section: Introductionmentioning
confidence: 99%